COVID-19 INFECTION AND VACCINATION IN PREGNANCY: A REVIEW - SHUKLA, AJAY KUMAR; MISRA, SAURAV (International Journal of Current Pharmaceutical Research, 2023)
A higher frequency of severe COVID-19 has been associated to pregnancy. Pregnant women are now regarded potentially sensitive to severe SARS-CoV-2 infection based on clinical experience with pregnancies complicated by infection by other coronaviruses, such as severe acute respiratory syndrome (SARS) and Middle Eastern Respiratory Syndrome. The immune system, respiratory system, cardiovascular function, and coagulation are all affected by physiological changes during pregnancy. The consequences of SARS-CoV-2 on implantation, foetal growth and development, labour, and new-born health have yet to be fully determined, and a focussed, global effort is needed to find out. Asymptomatic infection adds to the difficulty of providing services, preventing infection, and managing it. Finding safe immunizations that induce protective immune responses in pregnant and developing foetus is crucial. Although pregnancy safety data is rapidly increasing and no warning signals have been identified, further information about birth outcomes, particularly among those who were vaccinated earlier in pregnancy, is required. The rate of COVID-19 infection, maternal antibody response, placenta antibody transmission, and adverse effects after COVID-19 vaccination in pregnancy are all summarised in this review.